2018
DOI: 10.1002/adtp.201800082
|View full text |Cite
|
Sign up to set email alerts
|

Glycan Therapeutics: Resurrecting an Almost Pharma‐Forgotten Drug Class

Abstract: Despite their enormous potential, glycans as therapeutics yet remain a widely untapped drug class. This overview shares the viewpoint that glycans have been aptly termed the "dark matter" of biology and have thus been largely ignored for decades. Provided herein is a background on the multiple structures and functions of glycan therapeutics, and focuses on examples and case studies of the glycan therapeutics in clinical use or in a clinical development. Perspectives on various hurdles are also provided, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…28,[30][31][32][33] Recently, the relevance of GAGs to vaccines, protein, and antibody modications, and polyvalent glycan therapeutics has been highlighted by Paderi and co-workers. 34 Furthermore, due to the important role of proteoglycans in tumour progression and metastasis, GAGs have been applied to the design of novel anticancer therapeutics. 28,30,32 GAGs-based therapeutics are typically administered via the parenteral route as their bioavailability is compromised in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…28,[30][31][32][33] Recently, the relevance of GAGs to vaccines, protein, and antibody modications, and polyvalent glycan therapeutics has been highlighted by Paderi and co-workers. 34 Furthermore, due to the important role of proteoglycans in tumour progression and metastasis, GAGs have been applied to the design of novel anticancer therapeutics. 28,30,32 GAGs-based therapeutics are typically administered via the parenteral route as their bioavailability is compromised in the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we employed two preclinical stage bio therapeutics; GM-1111 and HepSYL. [33,38,39] GM-1111 is an anti-inflammatory agent engineered to treat chronic rhinosinusitis, as it inhibits multiple inflammatory mediators and requires topical intranasal administration route [56] and HepSYL is a new synthetic proteoglycan designed for oncotherapy applications. As such, a parenteral administration route is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Three different Zn-based metal-azolate frameworks (ZIF-8, ZIF-90, and MAF-7), of markedly different hydro-phobicity/-philicity, [36,37] were employed to encapsulate a selected set of GAGs-based therapeutics (HA, HP, CS, DS, GM-1111, and HepSYL, where the last two are synthetic drugs in preclinical development). [33,38,39] The encapsulation efficiencies (EE%) and therapeutic release profiles of each biocomposite were assessed as these are crucial information for the development of drug delivery systems. [25] For the first time we demonstrated that the release of pharmacologically relevant carbohydrate-based therapeutics can be performed using azolate-based MOF particles and the drug release properties can be precisely tuned by the judicious choice of the MOF material.…”
Section: Introductionmentioning
confidence: 99%
“…Glycosaminoglycans such as hyaluronic acid and heparin are ubiquitously present in tissues and function in various physiological processes [ 13 ]. Studies suggest the potential of chemically modified glycosaminoglycans as therapeutics for inflammatory diseases [ 14 ]. GM-1111 is a synthetic glycosaminoglycan molecule ( S1 Fig ) with anti-inflammatory effects by inhibiting innate immune molecules [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%